2004
DOI: 10.1007/s00330-004-2247-y
|View full text |Cite
|
Sign up to set email alerts
|

MRI findings in acute cerebellitis

Abstract: Acute cerebellitis is an inflammatory process involving the cerebellum. We report the clinical, CT and MRI features of four cases and a review of the literature. Bilateral diffuse hemispheric abnormalities represent the most common imaging presentations. Our observations demonstrate the various imaging appearances of acute cerebellitis. Simultaneous involvement of both hemispheres and the vermis has not been reported previously. The development of cerebellar atrophy following an initial normal MR imaging exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
99
1
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(110 citation statements)
references
References 27 publications
5
99
1
4
Order By: Relevance
“…Regardless of exact mechanism, our results may support the notion that pre-postnatal infections as well as vaccinations with measles may be important for ADHD. [43,44] Zeegers and colleagues reported that ADHD-HI is the most common type (38%), followed by ADHD-IA (26%) among HIV-infected SouthAfrican children while other studies of seropositivity among children with ADHD generally do not report subtypes. [45] In our sample, the most common diagnosis was ADHD-IA (43.3%), followed by ADHD-C (40%).…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of exact mechanism, our results may support the notion that pre-postnatal infections as well as vaccinations with measles may be important for ADHD. [43,44] Zeegers and colleagues reported that ADHD-HI is the most common type (38%), followed by ADHD-IA (26%) among HIV-infected SouthAfrican children while other studies of seropositivity among children with ADHD generally do not report subtypes. [45] In our sample, the most common diagnosis was ADHD-IA (43.3%), followed by ADHD-C (40%).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, high positivity in nasopharyngeal swab (CT value 22.26) led to consider strong link between Influenza and cerebellitis onset. Similarly, some authors reporting Influenza-associated cerebellitis could not detect Influenza RNA in CSF [7][8][9]. These findings suppose the absence of the direct effect of virus invasion and replication and suggest that neurologic manifestations such as encephalitis may be an indirect effect of the presence of the virus in the respiratory tract.…”
Section: Discussionmentioning
confidence: 74%
“…MRI is an excellent non invasive method to explore cerebellitis cases; it shows various patterns of cerebellar involvement [8]. Nevertheless, in some cases like our and cases from literature, it remains totally normal [9,11].…”
Section: Discussionmentioning
confidence: 77%
“…We have read with interest the recent article on the MR findings in acute cerebellitis [1]. We would like to add a rare case of a proven Lyme cerebellitis.…”
Section: Sirmentioning
confidence: 99%